We use the method of factorization to solve it
⇒ 5x2 - 10x + 3x - 6 = 0
⇒ 5x(x - 2) + 3(x - 2) = 0
⇒ (5x + 3)(x - 2) = 0
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
RELATED QUESTIONS :